The Influence Principal's Leadership, Welfare and School Facilities on Work Motivation of Indonesian Integrated Islamic School Network Elementary School Teachers (Educational Management, 2022)
The purpose of this study is to analyze how much influence, both jointly and individually, the principal's leadership, welfare and school facilities on the motivation of elementary school teachers of the Indonesian Integrated Islamic School Network, Pati Regional Coordinator. This research uses the survey method, the survey method is a quantitative research method used to obtain data that occurred in the past or present, about beliefs, opinions, characteristics, behavior of variable relationships and to test several hypotheses about socialogy variables. The results of the study explained that the leadership of the principal, the welfare of teachers, and school facilities had a positive and significant effect on teacher motivation with a consecutive sig score of 0.015; 0,000; and 0.000; (< 0.05), as well as the results of the F test with a significant value of 0.000 < 0.05, so it can be concluded that both individually and together the leadership of the principal, the welfare of teachers, and school facilities have a positive and significant effect on teacher motivation. The suggestion from this study is that for the use of leadership variables, in the next study it is hoped that it will not focus on leadership indicators, but should be done on existing types of leadership.